2015
DOI: 10.1007/s10265-015-0722-y
|View full text |Cite
|
Sign up to set email alerts
|

Environmental factors contribute to the formation and maintenance of the contact zone observed in deciduous broad-leaved tree species in Japan

Abstract: Contact zones are defined as areas where populations from different refugia meet during a postglacial expansion and distinct DNA lineages are mixedly distributed. In Japan, contact zones of various plants and animals were reported from the Kinki-Chugoku region. These contact zones appear to be maintained without any drastic topographic barriers such as those observed in the Alps and Pyrenees Mountains. In this study, the mechanisms underlying the formation and/or maintenance of these contact zones were investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…4). Reflecting the geographic arrangement of the archipelago, intraspecific lineages of temperate species are often reported to be differentiated along a north-south axis (Okaura et al, 2007;Sakaguchi et al, 2011;Sugahara et al, 2011;Clark et al, 2015;Tono et al, 2015). In the case of S. virgaurea complex, the demographic model, which suggested that the northern and southern lineages split first and then admixed in the central part of the island chain, was selected to account for genetic variation in the Japanese Archipelago.…”
Section: Phylogeographic History Of East Asian Goldenrodsmentioning
confidence: 99%
“…4). Reflecting the geographic arrangement of the archipelago, intraspecific lineages of temperate species are often reported to be differentiated along a north-south axis (Okaura et al, 2007;Sakaguchi et al, 2011;Sugahara et al, 2011;Clark et al, 2015;Tono et al, 2015). In the case of S. virgaurea complex, the demographic model, which suggested that the northern and southern lineages split first and then admixed in the central part of the island chain, was selected to account for genetic variation in the Japanese Archipelago.…”
Section: Phylogeographic History Of East Asian Goldenrodsmentioning
confidence: 99%
“…The Japanese Archipelago is thought to have been free of massive ice sheets during the last glacial maximum (LGM) with the exception of some high altitude areas [ 23 ]. Previous phylogenetic studies showed that the postglacial range expansion process may have caused secondary contact between formerly isolated lineages of Fagus crenata [ 24 ], Aesculus turbinata [ 25 ], Padus grayana , Euonymus oxyphyllus , Magnolia obovata , Carpinus tschonoskii , C. japonica , C. laxiflora [ 26 ], Platycrater arguta [ 27 ], Rubus palmatus, and R. grayanus [ 28 ]. Two ecologically distinct species of Vincetoxicum (Apocynaceae-Asclepiadoideae), V. atratum (Bunge) Morren et Decaisne and V. japonicum Morren et Decne., provide a suitable study system.…”
Section: Introductionmentioning
confidence: 99%
“…It is generally accepted that contact zones could be formed due to geographical factors such as the Alps and Pyrenees Mountains, but no such geographical factors have been recognized in the contact zone of Hyogo Prefecture. Tono et al (2015) theoretically address the question about the formation of contact zones in Hyogo Prefecture, using generalized additive models considering various environmental factors including climate and topography. The results indicate that "the pattern of low habitat suitability estimated by ecological niche modeling was the most appropriate for determining the location of the common contact zone", demonstrating its excellence by proposing a new global concept in the field of botanical geography.…”
mentioning
confidence: 99%